Fatigue and associated factors in multiple sclerosis patients in Latvia - Šetlere , S.; Abelsen , A.; Pastare , D.; Millers , A. (Neurologijos seminarai, 2018)
Background and objectives. Fatigue is one of the most common symptoms of multiple sclerosis (MS). The aim of this study was to determine the presence of fatigue in MS patients in Latvia and its relation to life style factors, neurological disability and depression.Material and methods. This cross-sectional study included 117 participants (44 patients with MS and 73 healthy control group). Applied research instruments were: Expanded Disability Status Scale (EDSS), Patient Health Questionnaire (PHQ-9), Fatigue Severity Scale (FSS), and the general questionnaire for the collection of socio-demographic, life style habits and clinical data constructed for the purposes of this study.Results. Mean FSS score was 3.9±1.9 in MS group. 26 (59.1%) patients had FSS score of 3.8 or more and were classified as a fatigue group (MSF) while 18 (40.9%) patients had FSS of 3.7 or less and were classified as a non-fatigue (MSNF) group. There was statistically significant difference between MSF and MSNF groups considering PHQ-9 score (p=0.019), FSS score (p
Keywords: multiple sclerosis; fatigue; depression